Design and Development of Smart Irrigation System in Paddy Field - Othman, Muhammad Sahimi; Afishah Alias, (Enhanced Knowledge in Sciences and Technology, 2026)
This study evaluates the performance of a water pump and solenoid valve at specific water levels, as well as the consistency and reliability of a prototype smart irrigation system for paddy fields under laboratory-controlled conditions. The prototype was tested using a hysteresis-based control logic, where the pump is activated when the water level is less than or equal to 2.0 cm and the solenoid valve is activated when the water level is greater than or equal to 3.0 cm, until the target water level of 2.5 cm is achieved. A repeatability test consisting of 10 consecutive cycles was conducted to evaluate whether the water level could be maintained within the range of 2.0–3.0 cm. The results show that the pump operated effectively at water levels between 0.0 cm and 2.4 cm, while the solenoid valve functioned as intended at water levels of 2.6 cm and above. In addition, the repeatability test revealed that the pump exhibited a low overshoot ranging from 0.00 cm to 0.10 cm, whereas the valve showed a higher overshoot ranging from 0.15 cm to 0.30 cm. Experimental result show that the water level was consistently maintained within the desired range of 2.0–3.0 cm. These findings demonstrate that the proposed prototype operates reliably at the predefined water levels and successfully maintains stable water level control under laboratory conditions.